2011
DOI: 10.1007/s00586-011-2039-4
|View full text |Cite
|
Sign up to set email alerts
|

Study to determine the presence of progenitor cells in the degenerated human cartilage endplates

Abstract: Introduction Cartilage endplate (CEP) degeneration is usually accompanied by loss of cellularity, and this loss may be a crucial key factor in initiation and development of degenerative disc disease. The study of cell types in degenerated CEP could help in understanding CEP etiopathogenesis, and may help in devising new treatments, especially if the presence of progenitor cells could be demonstrated. The aim of this study was to determine if progenitor cells existed in degenerated human CEP. Materials and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…This similar promoting migration to repair (PMR) effect has also been observed in many other tissues [13][14][15][16]. Until now, stem cells derived from various parts of the IVD such as the nucleus pulposus (NP), annulus fibrosus (AF), and cartilage endplate (CEP) have been isolated and characterized [17][18][19][20], whereas little is known about endogenous stem cell migration with respect to difficulties in labeling target stem cells in vivo.…”
Section: Introductionmentioning
confidence: 94%
“…This similar promoting migration to repair (PMR) effect has also been observed in many other tissues [13][14][15][16]. Until now, stem cells derived from various parts of the IVD such as the nucleus pulposus (NP), annulus fibrosus (AF), and cartilage endplate (CEP) have been isolated and characterized [17][18][19][20], whereas little is known about endogenous stem cell migration with respect to difficulties in labeling target stem cells in vivo.…”
Section: Introductionmentioning
confidence: 94%
“…A previous study by our group identified stem cells in human degenerated CEPs, which were named as CEP stem cells (CESCs) ( 15 ). The present study investigated the effects of cyclic tensile stretch on the apoptosis of CESCs and investigated the underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, OIM was used under both hypoxic and normoxic conditions. Under normoxic conditions, Huang et al ( 34 ) reported that OIM was able to significantly induce the osteogenic differentiation of CESCs, compared with normal growth medium. It was observed in Huang et al ( 34 ) study that the expression of osteogenic differentiation marker genes (RUNX2, ALP and OC) was decreased in the absence of OIM under normoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Under normoxic conditions, Huang et al ( 34 ) reported that OIM was able to significantly induce the osteogenic differentiation of CESCs, compared with normal growth medium. It was observed in Huang et al ( 34 ) study that the expression of osteogenic differentiation marker genes (RUNX2, ALP and OC) was decreased in the absence of OIM under normoxic conditions. In addition, previous studies have demonstrated that stem cell differentiation may be decreased in hypoxic conditions compared with normoxic conditions ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%